2017
DOI: 10.1158/1078-0432.ccr-16-2422
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Eribulin for Patients with Unresectable or Metastatic Liposarcoma Who Have Received a Prior Anthracycline-Containing Regimen

Abstract: On January 28, 2016, the FDA approved eribulin (Halaven; Eisai Inc.) for the treatment of patients with unresectable or metastatic liposarcoma who have received a prior anthracycline-containing regimen. The approval was based on results from a single, randomized, open-label, active-controlled trial (Trial E7389-G000-309) enrolling 452 patients with advanced, locally recurrent or metastatic liposarcoma or leiomyosarcoma. Patients were randomized to eribulin 1.4 mg/m intravenously (i.v.) on days 1 and 8 or dacar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 16 publications
(13 reference statements)
1
31
0
Order By: Relevance
“…Therefore, eribulin can be expected to improve OS in patients with liposarcoma. Further analyses showed eribulin to be effective for patients with dedifferentiated liposarcoma (HR 0.45; 95% CI 0.25–0.82) and pleomorphic liposarcoma (HR 0.21; 95% CI 0.06–0.76) [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, eribulin can be expected to improve OS in patients with liposarcoma. Further analyses showed eribulin to be effective for patients with dedifferentiated liposarcoma (HR 0.45; 95% CI 0.25–0.82) and pleomorphic liposarcoma (HR 0.21; 95% CI 0.06–0.76) [26]. …”
Section: Resultsmentioning
confidence: 99%
“…In that trial, eribulin prolonged the patients' OS compared to dacarbazine [24]. However, a subanalysis of the trial's data revealed that the OS benefit provided by eribulin was remarkable in the liposarcoma patients but not in the leiomyosarcoma patients [34,35]; as the result, FDA approved eribulin only for liposarcoma [36].…”
Section: Histology-based Chemotherapy Investigations Based On Clinicamentioning
confidence: 99%
“…Eribulin has recently been granted US FDA and EMA approval for the treatment of advanced LPS in patients pretreated with anthracycline chemotherapy. 58 It can be argued that the cost-effectiveness of the drug could be a potential obstacle to widespread use of eribulin, and this needs to be addressed in subsequent trials, including quality of life measurements. However, a Phase III trial has shown a significant survival benefit and an obvious question is the possible role of eribulin in the neoadjuvant/adjuvant setting and its role in the first-line setting compared to anthracycline therapy in LPS patients.…”
Section: Resultsmentioning
confidence: 99%